Metodologia inicial para quantificaç\~ao de sobreviventes aos homicídios perpetrados contra populaç\~ao negra no Brasil - Fernanda Lira Goes; Daniel A. Feitosa Lopes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– After the year 2000 homicides data shows an increasing in Brazil. Our attention directed to quantify those who are survivors or co-victims of homicide. Our initial exercise is a methodology to calculate the quantity of survivors from homicide against afro Brazilian black people. In 2010, for each homicide of an afro Brazilian black youth a minimum of 5 to 6 people were affected, causing a total of 82.535 survivors. At the same year, over 4 to 5 people were indirect victims of homicide against afro Brazilian black people summing an amount of 122.761 survivors.
Keywords: C13; 330; homicide; afro Brazilian black population; survivors; co-victims; Brazil